P157 Radioresistant and radiosensitive cells contribute to IL-18BP production in a model of macrophage activation syndrome. (March 2019) - Harel, M; Rodriguez, E; Girard-Guyonvarc'h, C; Palmer, G; Gabay, C
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Interleukin (IL)-18 is a pro-inflammatory cytokine, the activity of which is regulated by its natural inhibitor IL-18 binding protein (IL-18BP). If the balance between IL-18 and IL-18BP is dysregulated, abnormal levels of free bioactive IL-18 (fIL-18) are detected, such as in the sera of patients with macrophage activation syndrome (MAS). We showed that endogenous IL-18BP exerts a protective role in a murine model of MAS induced by repeated injections of the TLR9 agonist CpG. IL-18BP production is strongly increased in liver, lung, and spleen in this model, but its cellular origin is unknown. Objectives: To study the relative contribution of radioresistant and radiosensitive cells to IL-18BP production using bone marrow (BM) transfer experiments. Methods: Following whole-body irradiation, WT or Il18bp -/- recipient mice were reconstituted with WT or Il18bp -/- BM to create 4 groups of mice: WT recipient mice transferred with WT BM (WT/WT), WT/ Il18bp -/-, Il18bp - /- /WT, and Il18bp -/- / Il18bp -/- . BM chimeric mice were challenged with CpG injections on days 0, 2 and 4 and sacrificed on day 7. We assessed body weight during the course of the experiment, blood cell counts before and after CpG injections and spleen weight after sacrifice. Liver, lung and spleen mRNA levels of Il18, Il18bp, Ifng, and IFN-γ signature genes Cxcl9 and Ciita were determined by RT-qPCR. Circulating levels of IL-18BP, fIL-18, and CXCL9 were measured by ELISA. Results: The severity of CpG-induced MAS, as assessed by body weight changes, spleen weight and blood cell counts, was increased in Il18bp -/- / Il18bp -/- mice, but not significantly different between the three other groups. As reflected by a higher disease severity in Il18bp -/- / Il18bp -/- mice, an enhanced IFN-γ signature and elevated levels of circulating fIL-18 were observed in these mice. In the other groups, IL-18BP levels were still sufficient to inhibit IL-18 activity. Indeed, circulating IL-18BP levels dropped drastically only in the Il18bp -/- / Il18bp -/- group. Despite this, Il18bp mRNA levels, as assessed by RT-qPCR, varied in the different organs, consistent with the relative contribution of radioresistant versus radiosensitive cells. Indeed, following CpG stimulation radioresistant cells were the main contributors in liver (65%) and lung (90%), whereas radiosensitive cells were the primary source of IL-18BP in spleen (80%). Conclusions: Our results demonstrate that IL-18BP is produced by both radioresistant and radiosensitive cells and is present at high levels in the circulation to prevent the deleterious systemic effects of IL-18 in MAS. Disclosure of Interest: None declared.